2016
DOI: 10.1159/000442997
|View full text |Cite
|
Sign up to set email alerts
|

Which Aspects of Stroke Do Animal Models Capture? A Multitracer Micro-PET Study of Focal Ischemia with Endothelin-1

Abstract: Background: Cortical injections of the vasoconstrictor endothelin-1 (ET1) have widely been used to induce focal circumscribed ischemic lesions in the motor cortex of rodents in the context of stroke recovery studies. In order to apply this model correctly, it is essential to understand the time course of regional flow changes and of the development of penumbra and infarction. Methods: Multitracer micro-PET of ET1 focal ischemia in rats was performed using [11C]-flumazenil ([11C]FMZ) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Although endothelin is considered to play a key role in the induction of vasospasms after subarachnoid hemorrhage with subsequent infarcts in human patients, there are no data on its application in animal experiments to model this specific situation. Since ischemia develops slowly after endothelin-1 application and is accompanied only by minimal edema, this model again does not accurately mimic human stroke [112]. Similar to the photothrombotic model, it may be more useful for simulating lacunar stroke and for long-term studies with a focus on recovery mechanisms.…”
Section: Rodent Models Of Ischemic Strokementioning
confidence: 99%
“…Although endothelin is considered to play a key role in the induction of vasospasms after subarachnoid hemorrhage with subsequent infarcts in human patients, there are no data on its application in animal experiments to model this specific situation. Since ischemia develops slowly after endothelin-1 application and is accompanied only by minimal edema, this model again does not accurately mimic human stroke [112]. Similar to the photothrombotic model, it may be more useful for simulating lacunar stroke and for long-term studies with a focus on recovery mechanisms.…”
Section: Rodent Models Of Ischemic Strokementioning
confidence: 99%
“…We chose a model of focal cortical ischemia induced through local injection of the vasoconstrictor endothelin-1 (ET-1). Previous studies have shown that cortical injection of ET-1 recapitulates important pathophysiological aspects of human ischemia including significant reduction in cortical blood flow, persisting up to 23 h (Schirrmacher et al, 2016), leading to hypoperfused tissue and development of an infarcted area associated with neuronal cell loss (Windle et al, 2006;Nguemeni et al, 2015;Weishaupt et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…These needs have been met with poor therapeutic translation due to discrepencies in lissencephalic small animal stroke models including limited cerebral edema and swelling as well as variable MLS and mortality rates (108110). Specifically in endothelin-1 (ET-1) rodent stroke models, animals exhibit a dose-dependent ischemic lesion with marginal ischemic edema making this model less suited for studying acute stroke pathophysiology (111–114). In contrast, our pig stroke model exhibited increased ipsilateral hemipshere swelling due to the development of cytotoxic edema and consquent MLS within 24 hours post-stroke.…”
Section: Discussionmentioning
confidence: 99%